Positive Psychology and Sickle Cell Disease - Younger, Seth (International Journal of Innovative Research in Medical Science, 2019)
Positive psychology is described as a novel treatment for managing the negativism that accompanies pain in sickle cell disease. It has the potential to directly improve psychological well-being and health related outcomes and indirectly to support factors related to religion and spirituality by reinforcing positive strategies related to negative internal struggles. Motivational interviewing combined with positive psychology may have a role in addressing addiction to opioid analgesic medications routine employed in the management of sickle cell disease.